2020
DOI: 10.1101/2020.04.14.040964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tissue tropisms of avian influenza A viruses affect their spillovers from wild birds to pigs

Abstract: 32Wild aquatic birds maintain a large genetically diverse pool of influenza A viruses (IAVs), which can be 33 transmitted to lower mammals and ultimately humans. Through phenotypic analyses, only a small set of 34 avian IAVs replicated well in the epithelial cells of swine upper respiratory tracts, and these viruses were 35 shown to infect and cause virus shedding in pigs. Such a phenotypic trait appears to emerge randomly and 36 are distributed among IAVs across multiple avian species, geographic and temporal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(67 reference statements)
2
0
0
Order By: Relevance
“…This study is consistent with a recent study which reported on the wild bird-origin H4N6 viruses that had a high diversity in replication phenotypes in epithelial cells of the swine upper respiratory tract (53). Genetic analyses revealed that the genetic constellation of the RNP complex, rather than the receptor binding properties, was a major factor contributing to the observed phenotypic diversity (53). Nevertheless, the molecular basis for the efficient viral replication in DF-1 and A549 cells and the mouse lung of these H6 IAVs without prior adaptation needs to be further elucidated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study is consistent with a recent study which reported on the wild bird-origin H4N6 viruses that had a high diversity in replication phenotypes in epithelial cells of the swine upper respiratory tract (53). Genetic analyses revealed that the genetic constellation of the RNP complex, rather than the receptor binding properties, was a major factor contributing to the observed phenotypic diversity (53). Nevertheless, the molecular basis for the efficient viral replication in DF-1 and A549 cells and the mouse lung of these H6 IAVs without prior adaptation needs to be further elucidated.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, such distinct growth phenotypes were more likely to be associated with the genetic constellation, especially the RNP complex, but not with the receptor binding properties (Figure 2). This study is consistent with a recent study which reported on the wild bird-origin H4N6 viruses that had a high diversity in replication phenotypes in epithelial cells of the swine upper respiratory tract (53). Genetic analyses revealed that the genetic constellation of the RNP complex, rather than the receptor binding properties, was a major factor contributing to the observed phenotypic diversity (53).…”
Section: Discussionsupporting
confidence: 92%